2023
DOI: 10.3389/fpls.2023.1260625
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive detection of Pleurotus geesteranus strain degradation based on micro-hyperspectral imaging and machine learning

Xuan Wei,
Shiyang Liu,
Chuangyuan Xie
et al.

Abstract: In the production of edible fungi, the use of degraded strains in cultivation incurs significant economic losses. Based on micro-hyperspectral imaging and machine learning, this study proposes an early, nondestructive method for detecting different degradation degrees of Pleurotus geesteranus strains. In this study, an undegraded strain and three different degradation-level strains were used. During the mycelium growth, 600 micro-hyperspectral images were obtained. Based on the average transmittance spectra of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Pleurotus geesteranus , a globally cultivated edible fungus, plays a significant role in economies worldwide ( Singh et al, 2021 ; Wei et al, 2023 ). Analysis of P. geesteranus market prospects in 2024 showed that the global P. geesteranus market size is approximately 10.9 billion US dollars and is expected to grow at an annual rate of about 5%.…”
Section: Introductionmentioning
confidence: 99%
“…Pleurotus geesteranus , a globally cultivated edible fungus, plays a significant role in economies worldwide ( Singh et al, 2021 ; Wei et al, 2023 ). Analysis of P. geesteranus market prospects in 2024 showed that the global P. geesteranus market size is approximately 10.9 billion US dollars and is expected to grow at an annual rate of about 5%.…”
Section: Introductionmentioning
confidence: 99%